Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to simplify below expression or convert it to something simpler like $k^{n-1}$?

$$ k^0+k^1+k^2 + k^3+...+ k^{n-1} $$

share|cite|improve this question

marked as duplicate by Did, drhab, Ayman Hourieh, 900 sit-ups a day, Adam Hughes Jul 28 '14 at 15:57

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

What happens when you multiply your expression by $k$? – Mark Bennet Jul 28 '14 at 15:26
This is a finite geometric series. You have probably seen it before, maybe as $1+r+r^2+\cdots +r^{n-1}$. – André Nicolas Jul 28 '14 at 15:28
up vote 2 down vote accepted

Let $\displaystyle S=k^0+k^1+k^2+\cdots +k^{n-2}+k^{n-1}\ \ \ \ (1)$

If $ k=1, S=n$


$\displaystyle k\cdot S=k^1+k^2+k^3+\cdots +k^{n-1}+k^{n}\ \ \ \ (2)$

Now subtract $(2)$ from $(1)$ to find $\displaystyle (k-1)S=k^n-1$

Reference : Geometric progression

share|cite|improve this answer

This is a geometric series. If $k \neq 1$, it's sum can be derived as follows:

$S = k^0+k^1+k^2+\cdots+k^{n-1}$

$kS = k^1+k^2+k^3+\cdots+k^{n}$

$S-kS = k^0 - k^n$

$(1-k)S = 1-k^n$

$S = \dfrac{1-k^n}{1-k}$

share|cite|improve this answer

For $k \neq 1$:

$$\sum_{i=0}^{n-1} k^i=\frac{k^n-1}{k-1}$$

For $k=1$:

$$\sum_{i=0}^{n-1} 1=n$$

share|cite|improve this answer
@evinda what will be the result if $k=1?$ – lab bhattacharjee Jul 28 '14 at 15:28
@labbhattacharjee I edited my answer!!! – evinda Jul 28 '14 at 15:36

Hint: Let $S$ be the given sum, then find $kS$, and subtract the first from the second telescopingly...

share|cite|improve this answer

Not the answer you're looking for? Browse other questions tagged or ask your own question.